Mechanical Aspects of Deformation-Induced Surface Roughening in the Presence of Inclusions in a Subsurface Layer. Numerical Modeling - Romanova, Varvara; Dymnich, Ekaterina; Balokhonov, Ruslan; Zinovieva, Olga (Frontiers in Mechanical Engineering, 2020)
The mechanical aspects of deformation-induced surface roughening inherent in microstructural inhomogeneity are studied numerically using single inclusion models. Three-dimensional finite-element calculations of uniaxial tension are performed for a set of single inclusion models where a cubic-shaped inclusion is embedded into a homogeneous matrix. The inclusion-to-surface distance, tilt angle about the axis of tension, and the ratio between the matrix and inclusion elastic-plastic properties are varied in different combinations to study the effects which these parameters have on the development of out-of-plane surface displacements under uniaxial tension. It has been shown that all stress and strain tensor components in the vicinity of inclusions take on non-zero values, including those directed across the load axis. Thus, the free surface becomes rough under the action of internal forces originated from the inhomogeneous stress-strain fields. Some illustrative examples of surface roughening under uniaxial tension are shown for multiple ellipsoidal inclusions periodically arranged in a subsurface layer of an elastic-plastic material.